Industrial productivity - "Ashok, Pratap Singh" (New Delhi, 1988)
Industrial Productivity provides the much needed person-productivity linkage in studies of industrial productivity. This valuable study changes the focus in productivity studies from material inputs, raw materials, and technology to the human element of psychological and personality characteristics. In this timely volume Singh studies the level of productivity and associated personality characteristics and attitudinal variables of blue-collar industrial workers. The impacts of alienation, anxiety, and job involvement on productivity are examined. An excellent presentation of contemporary research and thinking in studies on industrialization, this work is particularly relevant for professionals and teachers in the fields of psychology, management, organization, and sociology. Further, its extensive bibliography of Indian studies on the subject of industrial productivity makes this work a valuable resource for the researcher and student in these fields. "A welcome attempt on the part of the author to meet the increasing need for such studies. The study will serve a basis for future studies and is light and fruit bearing nature which may go a long way in increasing industrial productivity in Indian business firms and organisations." --Journal of Contemporary Asia
Keywords: "Psychological, Industrial"